wisata Pengembangan Desa Wisata di Kelurahan Kemumu Kecamatan Arma Jaya Kabupaten Bengkulu Utara - Mirna Yunita; Warsa Sugandi; Edwar Edwar; Yuneva Syukur; Fevi Wira Citra; Nurmintan Silaban (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2020)
Against the background, the potential for tourism has not been managed into a single tourism package that can contribute to Local Original Revenue if it is managed properly. The purpose of this study is to formulate alternative strategies for developing tourism villages in Kemumu Village, Arma Jaya District, North Bengkulu by making physical, cultural and artificial potential into an attractive tour package. This type of research is a qualitative descriptive type conducted at the Office of Tourism and Culture of North Bengkulu Regency, Muara Bangkahulu District, Society and tourists. Determination of the informant is done purposively. Data collection is done through observation, interviews, and documentation. Data management is done through SWOT analysis. The results of the study can be formulated by six development strategies that the government must undertake: 1) improving access roads for connecting with other regions; 2) building supporting facilities around attractions (such as toilets, places of worship, restaurants, temporary dwellings, villas, parking lots and culture areas); 3) provide a place for cultural arts performances; 4) cooperating with farmers regarding permits to use terraced rice terraces or terraces for tourism activities (such as: tourists may participate in farming activities); 5) cooperating with private parties; 6) provide training to the community.